1994
DOI: 10.1128/jb.176.21.6509-6517.1994
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide dehydrogenase from the hyperthermophilic archaeon Pyrococcus furiosus: a new multifunctional enzyme involved in the reduction of elemental sulfur

Abstract: Pyrococcus furiosus is an anaerobic archaeon that grows optimally at 1000C by the fermentation of carbohydrates yielding acetate, C02, and H2 as the primary products. If elemental sulfur (SO) or polysulfide is added to the growth medium, H2S is also produced. The cytoplasmic hydrogenase of P. furiosus, which is responsible for H2 production with ferredoxin as the electron donor, has been shown to also catalyze the reduction of polysulfide to H2S (K. Ma, R. N. Schicho (33). The majority are strict anaerobes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 53 publications
3
116
0
2
Order By: Relevance
“…All g values are below 2.0, which is unusual. Similar EPR spectra have only been reported for putative [4Fe-4S] clusters in NADH-reduced glutamate synthase [21] and NADPH-reduced sul¢de dehydrogenase (ferredoxin NADPH oxidoreductase) [22]. As can be seen in the saturation plot (Fig.…”
Section: The [4fe-4s]supporting
confidence: 86%
“…All g values are below 2.0, which is unusual. Similar EPR spectra have only been reported for putative [4Fe-4S] clusters in NADH-reduced glutamate synthase [21] and NADPH-reduced sul¢de dehydrogenase (ferredoxin NADPH oxidoreductase) [22]. As can be seen in the saturation plot (Fig.…”
Section: The [4fe-4s]supporting
confidence: 86%
“…GSU3057 and GSU3058 were previously annotated as a homotetrameric NADPHdependent glutamate synthase and a putative dihydroorotate electron transfer subunit, respectively . However, no NADPH-dependent glutamate synthase activity could be detected in either wild-type or acetateadapted SfrAB-null extracts, and GSU3057 and GSU3058 were found to be 65.6 % and 65.2 % similar, respectively, to the a and b subunits of the NADPH-dependent ferredoxin oxidoreductase (FNOR) of Pyrococcus furiosus (Ma & Adams, 1994, 2001Schut et al, 2003). Phylogenetic analysis of GSU3057 and related proteins, including SfrB, which is 36 % similar, clearly indicated that GSU3057 was more closely related to the a subunit of P. furiosus FNOR than to the small subunits of the characterized glutamate synthases (Fig.…”
Section: Microarray Analysis Of the Acetate-adapted Sfrabnull Strainmentioning
confidence: 99%
“…Since S 8 is much less soluble and membranepermeable, it is thought that it is not directly reduced by bacteria, but is converted to a more soluble compound that serves as the actual substrate for reduction. [22][23][24] In the case of Wolinella succinogenes, polysulfide was found to be the soluble intermediate for sulfur reduction, and its polysulfide reductase was identified. 26) Polysulfide is generated chemically from S 8 and trace amounts of sulfide or polysulfide by the following reaction scheme: S n þ S m 2À !…”
Section: Discussionmentioning
confidence: 99%
“…To date, similar soluble NADH-dependent SRs have been found in Thiobacillus ferrooxidans 25) and Pyrococcus furiosus. 23) These organisms oxidize ferrous ion and organic acids respectively to generate ATP, and the resulting redox equivalent (NADH) was re-oxidized by the activity of SR. Similarly, fungal SR is thought to function in re-oxidizing NADH to NAD þ under O 2 -limited conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation